Mechanisms of resistance to neoleucinodes elegantalis (guenée) in wild germplasm of the genus solanum (2013)
Several phytosanitary problems affect tomato (Solanum lycopersicum) crops, one of the most important being the tomato fruit borer, which has caused losses of up to 70% in areas of the Valle del Cauca department (Colombia). To find resistance mechanisms to this pest, plants of three wild introductions of Solanum (PI134417, PI134418, LA1264) and the commercial cultivar Unapal-Maravilla were planted in a screenhouse. A completely randomized design was used with eight replicates. Five releases of N. elegantalis were carried out and the response was evaluated by the antixenosis or no preference test. Five racemes of each introduction were also suspended from the top of a field cage (1.8 x 1.5 x 1.5 m) to evaluate their response to six releases of the pest. For the two experiments, both an analysis of variance and analysis of means were performed. The average oviposition per plant was significantly higher in Unapal-Maravilla as compared with the wild introductions, and the average number of eggs per fruit was significantly lower in LA1264. The insects laid more eggs on the fruit surface ( and gt;70%). Glandular trichomes types I, IV and VI found in the wild introductions and their associated chemicals had an antibiotic and antixenotic effect on N. elegantalis.